The Effects of Emotional Intelligence on the Students’ Learning Outcomes in a State High School - Musnar Indra Daulay (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to find out the influences of emotional intelligence on the learning outcomes of high school students. The method used in this study is a qualitative case study. The participants of this study were 48 high school students in Pekanbaru. The data was taken by administering a questionnaire to those participants. The data were analysed qualitatively. The result informed that students’ emotional intelligence affects learning outcomes. The results also showed that emotional intelligence can make some useful contributions to students’ learning outcomes at schools, such as making them spiritful in learning and being able to manage emotions so that they can achieve learning goals. This contribution is indeed influential. However, because the factors that affect learning outcomes themselves are quite complex, and are not included in this aspect of the study, further studies are recommended conduct.